2021
DOI: 10.15420/ecr.2021.23
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Diagnosis of Coronary Functional Abnormalities

Abstract: Approximately one-half of patients undergoing diagnostic coronary angiography for angina have no significant coronary atherosclerotic stenosis. This clinical condition has recently been described as ischaemia with non-obstructive coronary arteries (INOCA). Coronary functional abnormalities are central to the pathogenesis of INOCA, including epicardial coronary spasm and coronary microvascular dysfunction composed of a variable combination of increased vasoconstrictive reactivity and/or reduced vasodilator func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“… 53 However, endothelium-dependent hyperpolarization factors (mainly hydrogen peroxide) seem to be the dominant modulators of resistance arteries, acting preferentially on prearterioles and arterioles instead of NO-mediated vasodilation of large conduit arteries. 58 Endothelium-independent mechanisms of impaired vasodilation are debated, but an attenuated response to vasodilators (eg, adenosine, dipyridamole, and papaverine), and an increase in the sympathetic autonomic activity that impairs the microcirculation, have been suggested as potential mechanisms. 48 Structural alterations (eg, luminal narrowing, vascular remodeling, vascular rarefication, or extramural compression) can also explain CMD via increased coronary microvascular resistance, particularly in the context of underlying cardiomyopathies and risk factors for CAD (eg, obesity, diabetes, hypertension, aging, dyslipidemia).…”
Section: Resultsmentioning
confidence: 99%
“… 53 However, endothelium-dependent hyperpolarization factors (mainly hydrogen peroxide) seem to be the dominant modulators of resistance arteries, acting preferentially on prearterioles and arterioles instead of NO-mediated vasodilation of large conduit arteries. 58 Endothelium-independent mechanisms of impaired vasodilation are debated, but an attenuated response to vasodilators (eg, adenosine, dipyridamole, and papaverine), and an increase in the sympathetic autonomic activity that impairs the microcirculation, have been suggested as potential mechanisms. 48 Structural alterations (eg, luminal narrowing, vascular remodeling, vascular rarefication, or extramural compression) can also explain CMD via increased coronary microvascular resistance, particularly in the context of underlying cardiomyopathies and risk factors for CAD (eg, obesity, diabetes, hypertension, aging, dyslipidemia).…”
Section: Resultsmentioning
confidence: 99%
“…The international diagnostic criteria for MVA were published in 2018. In addition, international guidelines have been established [34][35][36] that describe a systematic diagnostic process using invasive cardiac testing, including decreased a CFR, increased IMR, supposed MVS, and reduced blood flow velocity (contrast delay and/or thrombolysis in myocardial infarction [TIMI] frame count) [34][35][36][37][38] . MVS Mohri et al reported MVS in 1988 18) .…”
Section: Coronary Spasmmentioning
confidence: 99%
“…[ 16 ] the rate of ruptured plaques among 68 MINOCA patients was nearly 37%. The prevalence of plaque rupture could be even higher with more extensive use of higher-resolution imaging (es OCT), since other methods such as IVUS do not recognize plaque erosion [ 17 ]. Plaque erosion is the second most common cause of atherothrombosis (30–35%) [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Pathophysiology Of Minocamentioning
confidence: 99%